The effect of music as an ergogenic aid on average running pace / Noor Azma Iryani Abdull Aziz - Abdull Aziz, Noor Azma Iryani (Faculty of Sport Sciences and Recreation, 2020)
Objective: This study aim was to compare the effect of fast music and no music during 1.6 km on average running pace among Uitm basketball players. Method: Participants was given a brief explanation on how this test was conducted. They need to install running tracking application (STRAVA) on their smartphone that being used to measure their pace. During running they bring their smartphone with STRAVA application. The participant was given the selected song by researcher. They listen to the same playlist with the same volume that was set to 150 bpm to 200 bpm for fast music and no music given for no music condition. Each one of them wore earphone that connected to their smartphone. During running, it was depending on the participant on how they carried their phone either to hold by hand or to put it in their pocket. The song being played as soon as they start the test until they complete 1.6 km. After the experiment, the researcher collected all the data from the Strava app. The participant ended their session with cooling down conducted by the researcher. The gap between the first test and the second test is 24 hours. Results: Study shows there is a significant differences of effect between no music condition versus fast music condition on average running pace in data collected with value of 0.00 (p <0.05). Conclusion: Thus, the researcher concludes that music gave a positive impact to improve average running pace of UiTM basketball players.